2014
DOI: 10.1097/ta.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

The definition of polytrauma revisited

Abstract: Based on several consensus meetings and a database analysis, the expert panel proposes the following parameters for a definition of "polytrauma": significant injuries of three or more points in two or more different anatomic AIS regions in conjunction with one or more additional variables from the five physiologic parameters. Further validation of this proposal should occur, favorably by mutivariate analyses of these parameters in a separate data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
155
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(169 citation statements)
references
References 25 publications
0
155
0
14
Order By: Relevance
“…In this regard, multiple observational cohort studies from the orthopedic trauma group at MetroHealth in Cleveland have shown that early pelvic fracture fixation in stable or borderline resuscitated patients within 24 h of admission reduces the risk of complications and improves outcomes [139, 141, 144, 145]. Recently, a new definition of politrauma has been proposed by an international consensus group, which is based on injury severity and derangement of physiological parameters [153]. This new politrauma definition in conjunction with recently established grading systems [141] may provide further guidance towards the “ideal” timing of definitive pelvic fracture fixation, pending future validation studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, multiple observational cohort studies from the orthopedic trauma group at MetroHealth in Cleveland have shown that early pelvic fracture fixation in stable or borderline resuscitated patients within 24 h of admission reduces the risk of complications and improves outcomes [139, 141, 144, 145]. Recently, a new definition of politrauma has been proposed by an international consensus group, which is based on injury severity and derangement of physiological parameters [153]. This new politrauma definition in conjunction with recently established grading systems [141] may provide further guidance towards the “ideal” timing of definitive pelvic fracture fixation, pending future validation studies.…”
Section: Methodsmentioning
confidence: 99%
“…The global incidence rate is estimated at approximately 23 SCI cases per one million which equals to almost 180,000 new cases per annum [17, 18]. Apart from isolated TBI or SCI which occur quite rarely, it is also possible that these two conditions are concomitant and also accompanied by injuries to other body parts (extracranial or extraspinal injuries) which then means a multiple trauma in a patient [1924]. CNS trauma and associated extracranial and extraspinal injuries give an image of a debilitating condition, which does not only create physical and emotional costs for individuals.…”
Section: Introductionmentioning
confidence: 99%
“…They focused on the number of injuries, body regions or organ systems involved [8, 9], pattern or mechanism of injury [10, 11], injuries representing a threat to life [12, 13], ISS [14, 15], and threat to life plus ISS [16]. Since then, even further definitions have been published, wholly or partially based on the AIS [17, 18]. At present, the ISS is used as a standard classification of multiple trauma in the United States, many European countries, and Australia [17].…”
Section: Introductionmentioning
confidence: 99%